2008
DOI: 10.1089/cap.2007.0053
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Differentially Valued Rewards and Punishments in Youths with Bipolar Disorder or Severe Mood Dysregulation

Abstract: Background-Youths with chronic irritability and hyperarousal (i.e., severe mood dysregulation, SMD) have reward-and punishment-processing deficits distinct from those exhibited by children with episodic symptoms of mania (i.e., narrow-phenotype bipolar disorder, BD). Additionally, youths with SMD, like those with psychopathy, have prominent reactive aggression. Therefore, we hypothesized that SMD, but not BD, youths would be impaired on a decision-making task that has identified reward-and punishment-processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…Further, the boys with ODD exhibited lower skin conductance responses that were positively related to the speed with which they initiated the next trial. These findings contrast others that show no differences in reward or punishment processing between children with SMD and healthy controls (Rau et al, 2008). This suggests that characterizing RPE-related processes may provide a useful distinction between youth with SMD and those with ODD.…”
Section: Frustration Reward and Non-rewardcontrasting
confidence: 99%
See 1 more Smart Citation
“…Further, the boys with ODD exhibited lower skin conductance responses that were positively related to the speed with which they initiated the next trial. These findings contrast others that show no differences in reward or punishment processing between children with SMD and healthy controls (Rau et al, 2008). This suggests that characterizing RPE-related processes may provide a useful distinction between youth with SMD and those with ODD.…”
Section: Frustration Reward and Non-rewardcontrasting
confidence: 99%
“…However, the nature of these disruptions in DMDD is not easily determined from the extant literature as it appears to differ depending on the psychopathology studied. For example, children with irritability in the context of ODD exhibit reduced physiological responding to punishment (Luman et al, 2010; Matthys et al, 2004) that is not observed in studies of children with SMD (Rau et al, 2008). Similarly, children with disruptive behavior disorders including ODD do not show the typical decrease in striatal activity during non- reward (Gatzke-Kopp et al, 2009), while chronically, irritable youth (children with SMD), show an enhanced decrease in striatal activity in response to punishment (Deveney et al, 2013).…”
Section: Frustration Reward and Non-rewardmentioning
confidence: 91%
“…19 In addition, neuropsychological and imaging data gave further contributions to the differentiation between BD and chronic irritability. 2022 …”
Section: The Controversy About Irritability and Youth Bipolar Diagnosismentioning
confidence: 99%
“…Existing findings on reward dysregulation and BPSD diagnosis and mood symptoms in adolescence are mixed. On the one hand, differential reward learning tasks demonstrate no group differences between adolescents with BPSD from controls (Rau et al, 2008). On the other hand, adolescents with BPSD do exhibit impairment in tasks assessing the ability to adapt to changing reward contingencies (Dickstein et al, 2007; Dickstein et al, 2004; Gorrindo et al, 2005).…”
mentioning
confidence: 96%